DETERMINAN PERILAKU PENGELOLAAN SAMPAH PLASTIK DI MASA COVID-19 PADA MAHASISWA FIKES UPN VETERAN JAKARTA TAHUN 2022 - Mila Syehira Hutami (2022)
Data from the Ministry of Environment and Forestry in 2021 showed that plastic waste is the type of waste that ranks 2nd after food waste. Based on the results of preliminary studies, students have not managed plastic waste well. The aim of this study was to determine the determinants of Plastic Waste Management behavior during COVID-19 in FIKES UPN Veteran Jakarta students. This research is quantitative using a cross-sectional design. This study was conducted from April 2022 to June 2022. Sampling using proportionate random sampling technique with a total sample of 358 respondents. This research instrument used an online questionnaire. Based on bivariate analysis test (chi-square) factors related to plastic waste management behavior are sex (p-value = 0.011) with POR = 2.320 (95% CI 0.231-0.802), facilities and infrastructure (p-value = 0.002) with POR = 2.094 (1.332-3.292), and exposure to Information media (p-value = 0.022) with POR = 1,684 (1,098-2,582). Students are expected to increase knowledge and responsibility regarding plastic waste management through seminars, workshops, or other activities, and the faculty can accommodate these activities.